International Trade Effects: Lower Cost or Higher Quality? - Niem, Le Duc (Journal of Development and Administrative Studies, 2015)
In this paper, we modify the model of Liao (2008) to investigate the trade of quality differentiated goods between countries. We show that main effects of the trade are on quality improvement of all goods and the trade does not make the goods cheaper. Thus, we argue that New Trade Theory might not explain international trade that is based on quality differentiation. The Journal of Development and Administrative Studies, Vol. 22, No. 1-2, pp. 15-26, 2014